Morphotectonics of Jalisco and Oaxaca(1), México. - Cotilla-Rodríguez, Mario Octavio (2017)
Stress transfer from the subduction zone in the Pacific towards the continental interior has determined the current configuration of the morphotectonic rim for the Mexican environment. This process produced two transverse deformed zones, Puerto Vallarta and Tehuantepec. By using the Rantsman methodology, we found the same morphostructural and morphotectonic pattern with certain changes in Puerto Vallarta. We determined 6 blocks, 29 micro blocks, 6 main lineaments and 4 main intersections of lineaments. These elements are in correspondence with the zones with most significant activity and neotectonic deformation (~38000 km2), with a NW-SE main axis. We used the same technique for the Oaxaca region -adjacent to Tehuantepec, where 8 blocks, 25 micro blocks, 8 main lineaments and 14 major intersections of lineaments were identified. This set delimits a deformation zone (~ 40000 km2) with an E-W main axis. The analysis of seismicity, focal mechanisms, main active faults, fractures, lineaments, volcanic bodies and speed of plates convergence with the obtained models allows considering a rotation movement linked to Rivera microplate in Puerto Vallarta, while in Oaxaca there is a direct convergence of Cocos Plate -where there is no rotation.